An Insight in Developing Carrier-Free Immobilized Enzymes - Chauhan, Vivek; Kaushal, Diksha; Dhiman, Vivek Kumar; Kanwar, Shamsher Singh; Singh, Devendra; Dhiman, Vinay Kumar; Pandey, Himanshu (Frontiers in Bioengineering and Biotechnology, 2022)
Enzymes play vital roles in all organisms. The enzymatic process is progressively at its peak mainly for producing biochemical products with a higher value. The immobilization of enzymes can sometimes tremendously improve the outcome of biocatalytic processes making the product(s) relatively pure and economical. Carrier-free immobilized enzymes can increase the yield of the product and the stability of the enzyme in biocatalysis. Immobilized enzymes are easy to purify and the possibility of their reuse increases when compared to a free-enzyme system. Due to these varied advantages, researchers are tempted to explore carrier-free methods used for the immobilization of enzymes. In this review article, we have discussed various aspects of enzyme immobilization, approaches followed to design a process used for immobilization of an enzyme, and the advantages and disadvantages of various common processes used for enzyme immobilization.